2000
DOI: 10.2337/diabetes.49.9.1443
|View full text |Cite
|
Sign up to set email alerts
|

Identification of leptin-induced transcripts in the mouse hypothalamus.

Abstract: Long-form leptin receptor (OB-R L ) is a signal-transducing member of the cytokine receptor superfamily that is essential for mediating the effects of leptin on mammalian body weight homeostasis. At present, the range of transcriptional targets responsive to OB-R L activation, and consequently, the likely mediators of leptin action, remain undefined. In this report, we have used cDNA subtractive hybridization to identify transcripts induced by leptin in immortalized hypothalamic neurons expressing OB-R L . Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The enhanced leptin transgene expression depletes adipose tissue and depresses weight gain by increasing energy expenditures (White et al, 2000; Dhillon et al, 2001a,b; Bagnasco et al, 2002; Dube et al, 2002; Wang et al, 2010c). The injection of rAAV-lep increases hypothalamic leptin expression and moderates diet-induced hyperglycemia, hyperinsulinemia, and skeletal muscle insulin resistance (Buettner et al, 2000; Bagnasco et al, 2003; Lee et al, 2004).…”
Section: Leptin and Gene Therapymentioning
confidence: 99%
“…The enhanced leptin transgene expression depletes adipose tissue and depresses weight gain by increasing energy expenditures (White et al, 2000; Dhillon et al, 2001a,b; Bagnasco et al, 2002; Dube et al, 2002; Wang et al, 2010c). The injection of rAAV-lep increases hypothalamic leptin expression and moderates diet-induced hyperglycemia, hyperinsulinemia, and skeletal muscle insulin resistance (Buettner et al, 2000; Bagnasco et al, 2003; Lee et al, 2004).…”
Section: Leptin and Gene Therapymentioning
confidence: 99%
“…Among them, SOCS3 (suppressor of cytokine signaling 3) negatively regulates hypothalamic leptin signaling via the suppression of JAK2 activation and contributes to the development of a leptin-resistant state (15). Previously, White et al (2000) have identified four novel leptin-induced transcripts (LRG-47, T cell-specific guanine nucleotide triphosphate-binding protein, RC10-11, and Stra-13) from a hypothalamic neuronal cell line, GT1-7, stimulated with leptin (16). However, the roles of leptin-induced molecules in feeding behavior and energy metabolism remain unknown except for neuropeptides and SOCS3.…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 99%
“…Daily administration of recombinant leptin can partially or fully reverse these abnormal phenotypes (4 -10). Gene expression profiling in adipose tissue (11,12), skeletal muscle (13), hypothalamus (14), and pituitary (15) has been used to characterize differences in ob/ob and wild-type (wt) lean mice, and the response to leptin at the molecular level. Interestingly, hypercholesterolemia in ob/ob and db/db mice is due to elevated high-density lipoprotein (HDL) 1 levels (16).…”
mentioning
confidence: 99%